Pengaruh Beauty Influencer Terhadap Brand Awareness, Brand Image, Brand Attitude, dan Purchase Intention Beauty Product Lokal Indonesia - Ditta Shierlly Novierra (Jurnal Manajerial, 2023)
Background – Beauty influencers are now role models for beauty enthusiasts and becoming a trend. This new trend of beauty influencers combined with the rapid expansion of the beauty sector and the local brands or beauty products in Indonesia create an entirely new phenomenon. This research represents the current trends in Indonesia such as the era of digital, the adoption of social media in daily life, the rapid growth of local brands or beauty products, and the rise of influencers. Aim – The objective of this exploration of the beauty industry in Indonesia is to discover the effect of beauty influencers’ credibility on brand awareness, brand image, brand attitude, and purchase intention on local beauty products. Design / Methodology / Approach – The approach used in this study is quantitative. The sampling procedure was performed using non-probability purposive sampling combined with snowball sampling. The data was collected over a survey with a questionnaire. The data was analyzed using PLS-SEM in SmartPLS. Findings – The credibility of beauty influencers positively impacts brand awareness, brand image, as well as brand attitude of local beauty product brands. The brand awareness and brand image then positively influence the brand attitude which eventually positively impacts the purchase intention of local beauty product brands. Research Implication – Even though beauty influencers’ credibility does not directly impact the purchase intention, this research still recommends the company or marketer to engage the beauty influencers because they can influence brand awareness and brand image of beauty products through their reviews. If brand awareness is formed and a favorable brand image is created, it will boost the brand attitude which will ultimately affect the purchase intention of local beauty products or brands. Limitations – This research is limited to respondents in Java Island and credibility as the only indicator of beauty influencers. This research has not tested the causal relationship between variables simultaneously and has not tested the variables as intervening or moderator variables.